New firearms licensing guidance: GP responsibilities. (2nd January 2022) - Simsek, Ceylan; Ellison, Karen
Abstract : On 1 November 2021, new guidance for firearms licensing, including new arrangements for medical checks for firearm certificates, came into effect. This article will discuss the key considerations for GPs and the practice team